2020
DOI: 10.1038/s41598-019-57190-4
|View full text |Cite
|
Sign up to set email alerts
|

Poly-γ-glutamic acid induces system tolerance to drought stress by promoting abscisic acid accumulation in Brassica napus L.

Abstract: As a new plant biostimulant, poly-γ-glutamic acid (γ-PGA) may be an effective anti-drought agent that can efficiently alleviate the damage to plants under drought stress. In this study, the effects of γ-pGA on the physiological responses of oilseed rape (Brassica napus L.) seedlings under drought stress were investigated using hydroponics. Growth and development of the rape seedlings were significantly inhibited in a polyethylene glycol-simulated drought environment. However, 12 d after application of γ-PGA un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 56 publications
5
28
0
Order By: Relevance
“…The polypeptide has promising properties, such as its biodegradability, non-toxicity, water solubility and low production cost ( Chen et al, 2005 ). Xu et al (2020) define γ-PGA as an anti-drought agent that can efficiently alleviate damage to plants under drought stress by promoting the accumulation of abscisic acid in rape ( Brassica napus L.) as well as increasing enzymatic antioxidant activity and accumulation of proline. In addition, the polymer is also effective against salt and cold stress in rape ( Lei et al, 2016 ; Xu et al, 2017 ), by enhancing proline accumulation.…”
Section: Amino Acids and Other N -Containing Compomentioning
confidence: 99%
“…The polypeptide has promising properties, such as its biodegradability, non-toxicity, water solubility and low production cost ( Chen et al, 2005 ). Xu et al (2020) define γ-PGA as an anti-drought agent that can efficiently alleviate damage to plants under drought stress by promoting the accumulation of abscisic acid in rape ( Brassica napus L.) as well as increasing enzymatic antioxidant activity and accumulation of proline. In addition, the polymer is also effective against salt and cold stress in rape ( Lei et al, 2016 ; Xu et al, 2017 ), by enhancing proline accumulation.…”
Section: Amino Acids and Other N -Containing Compomentioning
confidence: 99%
“…Drought stress, one of the primary abiotic stresses, causes significant losses in agricultural production and will increase in both intensity and frequency with increasing planet temperature (Elizamar et al, 2013; Xu et al, 2020). In semiarid areas, rapeseed production is often affected by drought stress (Poveda, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Biofertilizer application promoted the elimination of ROS and, therefore, drops in LP values in treatments B3S and BAS. (Xu et al, 2020) also found a reduction in LP values under water stress conditions in Brassica rapa plants with the application of poly-γ-glutamic acid. This effect in the reduction of LP can be attributed to the increases in PR, and the enzymes POD and SOD, potential ROS scavengers, due to the applications of the biofertilizer.…”
Section: Discussionmentioning
confidence: 75%